STRATEGI PEMBERIAN MANASIK KESEHATAN HAJI DAN TATA CARANYA - Sholichah, Nisa Munadatus; Khotimah, Khusnul; Taqwa, Ussisa 'alat (Institut Agama Islam Negeri Metro, 2023)
The pilgrimage health ritual is for the physical and mental well-being of the pilgrims. The first step in the pilgrimage health ritual is a comprehensive health examination. The goal of the pilgrimage health ritual is to maintain the physical and mental health of the pilgrims so that they can perform the pilgrimage smoothly. The initial preparations of the pilgrims aim to reduce the risk of illness and ensure health during the pilgrimage. This research aims to outline health strategies for pilgrims before and after the pilgrimage through literature review. Pilgrims undergo psychological training to face the physical and emotional challenges of the pilgrimage. They are taught strategies to manage stress, stay motivated, and maintain inner peace to serve with focus and calmness. Additionally, the pillars of pilgrimage health also include vaccination and disease prevention. Pilgrims must receive specific vaccinations, such as meningitis and influenza, to prevent the spread of diseases. Infection prevention recommendations, such as regular handwashing, wearing masks, and avoiding contact with sick individuals, are also part of the health pillars of the pilgrimage.